Factors Related to Dignity of Hospitalized Older Persons, Southern Region - Patiwikran, Lawan; Kespichayawattana, Jiraporn (Nursing Research and Innovation Journal, 2017)
The descriptive research was conducted with the objectives of explore dignity of hospitalized older persons, Southern region and the relationships between functional ability, physical distress, psychological distress, and social support. The Model of Dignity in Illness was used as the theoretical framework of this study. The sample group consisted of 215 hospitalized older persons at the inpatients department, from July to October, 2015. Using the multistage sampling technique. Six questionnaires were used as research tools, including demographic data questionnaire, functional ability assessment from, questionnaire on physical distress, questionnaire on psychological distress, questionnaire on social support and questionnaire on dignity. Data were analyzed using descriptive statistics and Pearson’s Product Moment Correlation. Research results showed the hospitalized older persons perceived dignity were in moderate level and subscale of empowerment were at the high level. Physical distress and psychological distress were negative related to hospitalized older persons, Southern region with statistical significantly, functional ability and social support were positive related to to hospitalized older persons, Southern region with statistical significantly. The results of this study indicated that healthcare provider should be aware the importance of promoting care plan by assessing factors of older persons individuals, to adopt a strategy to promote the dignity care in older person.